(untitled) (Revista Chilena de Rehabilitación y Actividad Física, 2022)
Objective: In this study, the associations between the main risk factors with the suicide attempt were determined, in subjects who received their first attention in the hospital emergency service. Material and method: This were a descriptive study, in a sample of 797 cases treated in the emergency department, through self-harm reports, for the years 2017-2018, the association between sex, type of method and the psychiatric diagnoses with attempted suicide. For the associations, the Chi-Square test and odds ratio [OR] were used for risk analysis, for the comparison of cases per year, the Student’s T-test was used. Results: Our results showed the existence of an association between suicide attempt, sex, age group, type of method, psychiatric diagnosis and drug. The risk of suicide attempt increased in the depression variable (OR=1.4; p<0.05), with a higher risk for females (OR=1.8; p<0.05). Regarding the difference per year, the suicide attempt increased by 19.4 % (p = 0.000; CI95 %) from 2017 to 2018. Conclusion: The suicide attempt has a significant association with the female sex and with the presence of depression, in addition to the latter being the ones that generate a greater risk for suicide attempts.